UPM – making of a research university. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2004)
Universiti Putra Malaysia (UPM) has made significant progress since it started as a School of Agriculture in 1931. Over the passed decades, it has greatly transformed itself into one of the largest established premier institutions embracing research as an integral part of its mission, with agro-bio as our niche. Having set a blueprint for e-university to attain a world-class status, our vision is clear. Our course is set. Sharing Malaysia's destiny in line with UPM's 10-year strategic plan, spanning from 2001 to 2010, and now setting ourselves to becoming a top research university is a worthy endeavor and an exciting prospect.